The Effect of rs80860411 Polymorphism on Fattening, Slaughter, and Pork Quality Traits in Polish Large White and Pulawska Breeds - Anna Antonyk; Arkadiusz Terman; Mirosław Tyra; Grzegorz Żak; Daniel Polasik; Magdalena Szyndler-Nędza; Hanna Kulig; Andrzej Dybus (Animals)
The intergenic SNP (single-nucleotide polymorphism) rs80860411A>C was identified as a major QTL for drip loss measured on semimembranosus muscle (SM) in pigs. The SNP is located near the GALNT15. The purpose of this study was to analyze the association between rs80860411A>C and fattening, slaughter, and quality traits of Polish pigs. This study was conducted on 235 individuals belonging to two breeds, Polish Large White (n = 187) and Pulawska (n = 48). The rs80860411 genotypes were determined using the PCR-RFLP method. Association analysis was performed for each breed separately. It was shown that rs80860411A>C had a significant effect on fattening performance traits, on several slaughter performance traits, including width of the loin eye and carcass meat content (p ≤ 0.01, p ≤ 0.05), as well as on meat color—redness (a*) (p ≤ 0,05) in Pulawska breed. The obtained results indicate that the studied SNP has the potential to be a QTN and could be included in pig selection programs, especially in Pulawska pigs.